2020
DOI: 10.1159/000512502
|View full text |Cite
|
Sign up to set email alerts
|

ctDNA in Neuroendocrine Carcinoma of Gastroenteropancreatic Origin or of Unknown Primary: The CIRCAN-NEC Pilot Study

Abstract: Introduction: Gastroenteropancreatic neuroendocrine carcinomas (GEPNEC) are characterised by a heterogeneous molecular profile and a poor prognosis. Circulating tumour DNA (ctDNA) analysis may be useful for NEC management. This study aimed at describing ctDNA mutations, to assess their predictive value for response to chemotherapies, and their change according to disease progression. Methods: The CIRCAN-NEC study included patients with GEPNEC or NEC from an unknown primary, scheduled to begin first or second-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…Tumors showed heterogeneous alterations, with the exception of the TP53 mutation which was present in 83% of cases. There was a 44% agreement between ctDNA and tissue NGS alterations [67]. Data is lacking for ctDNA in resected NEC due to the rarity of this situation.…”
Section: Circulating Tumor Deoxyribonucleic Acid (Dna)mentioning
confidence: 82%
See 1 more Smart Citation
“…Tumors showed heterogeneous alterations, with the exception of the TP53 mutation which was present in 83% of cases. There was a 44% agreement between ctDNA and tissue NGS alterations [67]. Data is lacking for ctDNA in resected NEC due to the rarity of this situation.…”
Section: Circulating Tumor Deoxyribonucleic Acid (Dna)mentioning
confidence: 82%
“…There is little data regarding ctDNA in NEC management. Recently, a pilot study has shown that for 24 patients with NEC, 22 had at least one driver mutation [67]. Tumors showed heterogeneous alterations, with the exception of the TP53 mutation which was present in 83% of cases.…”
Section: Circulating Tumor Deoxyribonucleic Acid (Dna)mentioning
confidence: 99%
“…Additionally, there is still limited knowledge of the EP-NEC biology [6]. A number of studies have attempted to elucidate the molecular landscape of EP-NECs over the past few years [21][22][23][24][25], as these cancers have been gaining more attention in the scientific community. Accumulating evidence indicates that besides a common element of NE biology (e.g., high prevalence of TP53 and RB1 loss), EP-NECs exhibit typical molecular traits of adenocarcinomas from the same sites of origin [8].…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question as to whether treatment strategies which are established for the latter could also find application in EP-NECs. In the CIRCAN-NEC study [24], reporting on circulating tumour DNA (ctDNA) analysis in patients with advanced-stage GEP-or CUP-NEC, the most commonly mutated genes were TP53 and RB1, but also genes associated with GEP adenocarcinoma pathogenesis (e.g., KRAS, BRAF and APC). Interestingly, those cases classified as "adenocarcinoma-like" based on their ctDNA profile showed less durable responses to the first-line platinum/etoposide chemotherapy, compared to cases which did not harbour any adenocarcinoma-associated mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The CIRCAN-NEC pilot study investigated ctDNA mutations in the blood samples of 24 patients with a diagnosis of GEP NECs or NEC from an unknown primary, to assess the sensitivity of ctDNA in characterising genetic alterations, and their value in predicting response to chemotherapy. Preliminary results from the published abstract have demonstrated mutations in TP53 , RB1 , and KRAS, and some also had an ‘adenocarcinoma-like’ profile [ 56 ]. The concordance between the ctDNA mutation rate and immunohistochemistry findings was 64% for TP53 and 14% for RB1.…”
Section: Cell Free Dna (Cfdna) and Circulating Tumour Dna (Ctdna)mentioning
confidence: 99%